Changes in cortical activation and excitability during prolonged cycling exercise - Jubeau, M.; Rupp, T.; Perrey, S.; Temesi, J.; Wuyam, B.; Verges, S.; Millet, G. Y. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: It has been previously demonstrated that prolonged cycling exercise induces muscle fatigue, i.e. decrease of maximal voluntary contraction (MVC) force, due to alterations of both peripheral mechanisms (contractile properties and action potential propagation) and central drive (1). However, it remains unknown whether a supraspinal deficit occurs throughout prolonged exercise. Therefore, the purpose of this study was to evaluate cortical excitability and cortical activation before, during and after a 4-h cycling exercise. Methods: Ten healthy subjects performed three 80-min bouts on an ergocycle at 45% of their maximal aerobic power separated by 25 min bouts of neuromuscular function (NMF) testing. Before exercise and immediately after each bout, NMF was evaluated on the right quadriceps femoris under isometric conditions. Transcranial magnetic stimulation was used to assess cortical voluntary activation (VA, as proposed by 2), cortical excitability via motor evoked potential (MEP) and intracortical inhibition by cortical silent period (CSP). Electrical stimulation of the femoral nerve (single and paired stimuli) was used to measure peripheral VA and muscle properties. Mechanical and electromyographic (vastus lateralis, vastus medialis and rectus femoris) data were recorded during all NMF testing procedures. Results: MVC was significantly reduced after the first bout (P < 0.01) and was further decreased (-25%, P < 0.001) at the end of exercise. As expected, single twitch and doublet peak torque were depressed after the first bout and remained so throughout the protocol (P < 0.001). M-wave amplitudes were also reduced for the three studied muscles (P < 0.01). In contrast, CSP and raw MEP amplitude remained unchanged throughout the protocol. However, MEP normalized to maximal M-wave significantly increased after the first cycling bout and remained elevated. Finally, a significant decrease in both cortical and peripheral VA was observed at the end of exercise (~ -7%, P < 0.01) but these changes were not correlated. Discussion: Alterations of both central drive and muscle function explain the large strength loss after prolonged cycling exercise. The main findings of this study are that reductions in peripheral VA measured here and in previous fatigue studies in cycling are partly explained by a deficit at the corticospinal level despite increased corticospinal excitability and similar intracortical inhibition.